Proceedings of the Symposium on Time Series Analysis held at Brown University, June 11-14, 1962 (New York : John Wiley & Sons, 1963)
The Symposium covered a broad area in terms of theory and application. This book will contribute to a healthy cross fertilization of ideas in the theory and practice.
aia 5/12/17
Loans
Keywords: Time Series Analysis----- Congresses; Regression Analysis---- Congresses